2018
DOI: 10.1002/eat.22889
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviors in adolescents with type 1 diabetes: A cross‐sectional population‐based study in Italy

Abstract: A specific clinical profile of DEPS-R-positive was identified. A multidisciplinary clinical approach aimed to normalize eating behaviors and enhance self-esteem should be used to prevent the onset of these behaviors, and continuous educational programs are needed to promote healthy behaviors and lifestyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
39
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 34 publications
15
39
1
2
Order By: Relevance
“…As confirmed by both eating problem measures adopted in this study (i.e., diabetes-specific measure and generic tool) and in line with previous evidence from Italian samples (Pinna et al, 2017;Cherubini et al, 2018;Troncone et al, 2019), DEBs were more frequent in adolescents with T1D than in healthy peers. DEBs were found in both genders, although -as reported in DEB studies with adolescents from the general and the T1D population (Neumark-Sztainer et al, 2011;Wisting et al, 2013;Baechle et al, 2014;Colton et al, 2015) -they were found to a greater extent in girls than in boys, regardless of health status.…”
Section: Disordered Eating Behaviors (Debs)supporting
confidence: 91%
See 1 more Smart Citation
“…As confirmed by both eating problem measures adopted in this study (i.e., diabetes-specific measure and generic tool) and in line with previous evidence from Italian samples (Pinna et al, 2017;Cherubini et al, 2018;Troncone et al, 2019), DEBs were more frequent in adolescents with T1D than in healthy peers. DEBs were found in both genders, although -as reported in DEB studies with adolescents from the general and the T1D population (Neumark-Sztainer et al, 2011;Wisting et al, 2013;Baechle et al, 2014;Colton et al, 2015) -they were found to a greater extent in girls than in boys, regardless of health status.…”
Section: Disordered Eating Behaviors (Debs)supporting
confidence: 91%
“…Similarly, the association between DEBs and lower SES, poorer glycemic control, and duration of illness confirmed what has already been reported by previous studies on adolescents with T1D (Young et al, 2013;Pinhas-Hamiel et al, 2015;Cherubini et al, 2018;Troncone et al, 2019).…”
Section: Body Image Problems and Debssupporting
confidence: 90%
“…This contradicts the general assumption that "social distancing" and isolation-creating anxiety, sadness, anger, and perception/sense of loneliness-may have a negative psychological impact [1] and even exacerbate eating disorder risks [44], further compromising individuals with psychopathological and eating problems [27,28,45,46]. Furthermore, recent evidence from Italian samples [47][48][49][50][51] describe youths with T1D as suffering from DEBs more frequently than healthy peers. In contrast, children and adolescents with T1D evaluated in this study did not show higher DEBs than controls.…”
Section: Discussionmentioning
confidence: 96%
“…Based on other studies suggesting the prevalence of disordered eating of 27% for boys and 42% for girls in T1D,31 we estimated that we would need to screen approximately 50 adolescents to enrol at least 20 adolescents (who score over the cut-off on the DEPS-R). We will use the observed changes in psychological outcomes (eg, DEPS-R) and physical health outcomes to calculate the required sample size for a subsequent fully powered RCT.…”
Section: Methods and Analysismentioning
confidence: 99%